KAJIAN SOSIAL EKONOMI MASYARAKAT PETANI PERKEBUNAN DI DALAM DAN DI SEKITAR HUTAN - SYAFRU KEMALA (Jurnal Penelitian Tanaman Industri, 2002)
The contribution of estate subsector to the income of the farmers living in the forest and in the ■urronding area is still low. This study was caried out socioeconomic and their roles in improving their welfare. The study was conducted rom August to October 2000 in three forest management systems (1) system of Hak Pengusahaan Hutan (HPH) which was represented by Sukamulya and Siabu villages, Bangkinang, Kampar District, and Rambah Jaya Village, Rambah Hilir, Rokan Hulu District; (2) System of Hutan Taman Nasional which was represented by Andongrejo and Eaat Java Province; (3) System of Hutan Sosial (Perum Perhutani) which waa represented by Kedung Urang Village, Cilacap Subdistrict, and Sawangan Village, Jeruk Legi Subdistrict, Cilacap District, Central Java Province. Sample villages were chosen through purpose sampling method. The data were analyzed desciptively and comparative and approacted through socioeconomic indicators and criteria. The results of the research indicated that the socioeconomic condition of the estate farmers living in the forest and in the surrounding are was lower compared to those of the area was lower compared to those of the rice farmers and others farmers. The average income of the estate farmers ranged between Rp 360 860.00 and Rp 523 550.00. The range of income distribution (Gini ratio) was 0.295 to 0.430. Out of the three forest mana¬ gement systems, the village of Hutan Taman Nasional was better than those of two other systems, where the income level waa Rp 432 000.00 Gini ratio was 0.320; structure and inrastucture was moderate.